Trading voices : the European Union in international commercial negotiations - Meunier, Sophie (Princeton University Press, 2005)
"Trading Voices is the most comprehensive book about the politics of trade policy in the EU and the role of the EU as a central actor in international commercial negotiations. Sophie Meunier explores how this pooling of trade policy-making and external representation affects the EU's bargaining power in international trade talks. Using institutionalist analysis, she argues that its complex institutional procedures and multiple masters have, more than once, forced its trade partners to give in to an EU speaking with a single voice."